FABRICATION AND CHARACTERIZATION OF LTCC BASED ON TALK GLASSES (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
In this work, fabrication of low temperature co-fired (LTCC) with different Talc content is performed. Density and mechanical characterization of the prepared samples has been examined. Three series of low temperature co-fired ceramics have been prepared. The glass part of these composites contains talc to enhance the mechanical properties. The densities, hardness and splitting strength are measured for these series to monitor the effect of composition on their properties. It is shown that the third series (Base3; Flint 25%, talc 35%, Pota ash 8%, Soda ash 12%, and Boric Acid 20%) of the higher talc content shoes the better densities and mechanical properties. The results are explained in terms of better balance of the ceramic-class content that enhances the measured properties.